Pendampingan Waste Accounting Sederhana pada UMKM di Desa Kandolo untuk Mendukung SDGs 12 - Muhammad Rinaldi; Yana Ulfah; Melda Aulia Ramadhani (Jurnal Bersama Pengabdian Kepada Masyarakat (SAMAMAS), 2026)
This community service activity was initiated by the limited understanding of simple waste accounting among the Joint Business Group (KUBE) Jahe Merah Gula Aren in Kandolo Village, East Kutai Regency. As a result, business waste had not been recognized as a cost component and was not adequately recorded. The activity aimed to improve the partner’s understanding and capacity to record business waste in a simple manner that was appropriate to the needs of a micro-enterprise. The program was implemented in August 2025 at the partner’s production site through a review of the production flow, concept reinforcement, guided discussions, identification of waste as a cost component, recording practice, and assistance in using a simple recording format. The results indicate a shift in the partner’s perspective on waste, from merely being seen as production residue to being understood as part of resource use associated with business costs. The partner also began to identify sources of waste at different stages of production and to use a simple waste accounting recording format designed in accordance with the administrative capacity of a micro-enterprise. These findings suggest that simplifying the recording instrument is a more practical and realistic approach for the partner than introducing a complex accounting system. This activity provides an initial foundation for more orderly, efficient, and responsible waste management, although further assistance is still needed to ensure consistent implementation.